Sensory approaches in psychiatric units: Patterns and influences of use in one Australian health region. (15th June 2022) - Wright, Lisa; Meredith, Pamela; Bennett, Sally
Abstract: Background/aim: Australian guidelines and policies recommend the use of sensory approaches in mental health care. Nevertheless, many Australian psychiatric units report difficulty sustaining these approaches. To inform efforts to close the gap between recommendations and practice, the aim of this study was to understand the patterns of use of sensory approaches and what demographic and clinical factors influence their use, across one health region in Queensland, Australia. Methods: Using a cross‐sectional survey design, a custom‐designed questionnaire was distributed via email and in paper form to health professionals and peer support workers working in acute, secure, and community care psychiatric units across one health region. Information on demographics and the use of various sensory interventions was gathered utilising both open‐ended and Likert scale questions. Results: Useable questionnaires were collected from 183 participants from various disciplines (77% nursing). The majority reported using sensory approaches with a limited number of consumers, and almost 9% never used the approach. Activity‐based sensory interventions and sensory equipment were most often used, whereas sensory assessments, sensory plans, and sensory groups were least used. Sensory interventions were mainly used to reduce consumer anxiety and agitation and to assist with emotional regulation. Factors positively correlated with frequency of use for all interventions were discipline (occupational therapy); working in an acute inpatient unit; and training in sensory approaches. Age was negatively correlated with frequency of use only for weighted modalities. Conclusions: This study revealed that sensory approaches were used by most staff though with a limited proportion of consumers in psychiatric units in one large metropolitan health service. It provides insights into the factors influencing frequency of use, highlighting the importance of training in sensory approaches and access to occupational therapists. With this knowledge, we can work towards closing the gap between recommendations and the practice of sensory approaches.